Adaptation strategies of desert riparian forest vegetation in response to drought stress. Issue 6 (19th July 2013) - Chen, Yaning; Zhou, Honghua; Chen, Yapeng; Shen, Yanjun; Chen, Yaning; Liu, Changming
ABSTRACT In this paper, we discuss the adaptation mechanisms of desert riparian forest vegetation's responses to drought stress. Ecological and physiological parameters are presented, including coverage, density and species diversity. Also investigated are the photosynthesis, fluorescent parameters, leaf water potential, leaf proline (PRO), soluble sugar, malondialdehyde, superoxide dismutase (SOD), peroxidase (POD) and abscisic acid (ABA) of the main constructive species at various buried groundwater depths of the Tarim River's lower reaches. The results reveal a close relationship between vegetation and groundwater depth and show that the most appropriate groundwater depths for the optimal composition and structure of plant communities is 2–6 m. For the main constructive species, Populus euphratica and Tamarixspp., the most appropriate groundwater depths and the critical depths are 4 and 8 m for P. euphratica and 6 and 10 m for Tamarixspp., respectively. However, when groundwater depths exceed 4 m for P. euphratica or 6 m for Tamarixspp., the plants suffer drought stress. During moderate or extreme drought stress, P. euphratica and Tamarixspp. rapidly accumulate PRO, soluble sugar, SOD and ABA in their leaves, thereby reducing leaf water potential and stomatal conductance, enhancing osmoregulation and alleviating the esterification of cell membranes. Such a response decreases the yield as well as the photosynthetic and electron transport rate, thus improving the efficiency of water utilization. Complementary actions in resisting drought stress likewise occurred between SOD activity and POD activity, and between the contents of PRO and soluble sugar in P. euphratica and Tamarixspp. leaf cells. In the main, P. euphratica accumulated a large amount of soluble sugar for osmoregulation to counter drought stress, whereas Tamarixspp. accumulated a large volume of PRO. When suffering extreme drought stress, Tamarixspp. enhanced its POD activity. Copyright © 2013 John Wiley & Sons, Ltd.